Intellectual capital and company performance: the moderating effects of business strategy in the context of resource-based and knowledge-based theories / Aminuddin Shamsuddin - Shamsuddin, Aminuddin (Institute of Graduate Studies, UiTM, 2018)
Malaysia aspired to transform its economy from an industralizing economy into a knowledge-based economy that is expected to help in achieving its Vision 2020. However, the new competitive landscape brought about by the shift into knowledge economy has presented companies with unprecedented strategic challenges for leveraging and making knowledge more productive as a competitive resource in a complex and unpredictable environment. Competitive success of businesses is depending more on strategic management of intellectual capital (IC) and less on the strategic allocation of physical and financial resources. The Resource-based Theory views that company resources such as IC are the key drivers of competitive advantages and vital to company financial performance. Meanwhile, the Knowledge-based Theory further supports the view that unique sets of knowledge, and the distinctive ways in which knowledge is integrated and organised by the company, can generate capabilities that either create or support a company’s competitive advantage. With this development, companies have begun to recognise the importance of IC. This study investigated IC within an organisational context by examining IC and how it impacted company’s performance. The initial focus was on determining the main effect between IC and performance; followed by exploring the individual effects of the IC components on performance. The findings led to the development of an IC index for Malaysian companies. Thus, the study came up with a model named Malaysian Intellectual Capital Index (My-ICI)…